Special Issue: Characterizations of Three-Dimensional Surfaces at Micro/Nanoscale - Ţălu, Ştefan (Applied sciences, 2022)
[1] compared several platinum–carbon (PtC) nano-tips by focusing ion beam-induced deposition (FIBID) and focused electron beam-induced deposition (FEBID) using high-resolution transmission electron microscopy (HRTEM) analysis. The authors stated that the deposition process of GdMnO3 thin films and the subsequent sintering at 850 °C produces films with interesting topographic properties that can be used to improve the fabrication process of thin films based on systems involving rare earths, which are known as excellent multiferroic materials for technological applications. Haub, M.; Günther, T.; Bogner, M.; Zimmermann, A. Investigation of Focused Ion and Electron Beam Platinum Carbon Nano-Tips with Transmission Electron Microscopy for Quantum Tunneling Vacuum Gap Applications.